Web-Based Complaint Handling System:A Pre-Post Cohort Evaluation of E-Service Quality - Melati Oktafiyani; Etika Kartikadarma; Handy Nur Cahya; Wikan Isthika; Dayangku Azriani binti Awang Ismail (International Journal of Artificial Intelligence Research, 2026)
Customer complaint management remains a critical challenge because fragmented communication channels act as an informational “black box” for consumers, increasing uncertainty and weakening organizational trust. While prior studies focus primarily on technical deployment or post-adoption satisfaction, empirical evidence isolating how system-driven transparency drives trust recovery remains scarce. This study designs and evaluates a web-based Customer Complaint Handling System (CCHS) built on a three-tier Model–View–Controller (MVC) architecture to address this gap. Methodologically, a single-cohort longitudinal pretest–posttest design was executed involving 84 identical participants tracked over two sequential 30-day operational periods. Data were collected using a 20-item instrument covering five dimensions adapted from Electronic Service Quality (E-S-QUAL) and Information Systems Success frameworks. Reliability was confirmed via Cronbach’s alpha (?pre = 0.842; ?post = 0.891). Quantitative tracking revealed highly significant positive shifts across all dimensions (p < 0.001) following system implementation. Notably, Transparency & Information achieved the most substantial growth (? = +3.09; 213.1%), heavily driven by real-time status visibility (? = +3.40), while Satisfaction & Trust increased by +2.44 points (120.8%). Conversely, Fairness & Resolution Quality exhibited bounded improvement (? = +1.10), proving that automated architectures act as operational facilitators rather than replacements for human judgment. These findings demonstrate that digital process visibility operates as an independent driver of trust recovery, offering actionable guidance for digital service governance.